EXERGOECONOMIC OPTIMIZATION OF POWER SYSTEMS - Bolbot, Igor (Енергетика і автоматика, 2016)
Substantive provisions of Exergoeconomic Optimization Method are shown here. And also Algorithms of Estimation of Power and Economic Efficiency Parameters of analysed system are represented in this work.